The Impact of AI Assistants on Optimising Business Processes and Increasing Productivity of Enterprises in Ukraine - Khodorkovskyi, Oleksandr (Здобутки економіки: перспективи та інновації, 2025)
Artificial intelligent assistants (AI assistants) are increasingly used in management, marketing, customer service, and task automation, contributing to the productivity of enterprises. However, in Ukraine, the adoption of such technologies is accompanied by specific challenges, including limited access to knowledge, financial barriers, and ethical issues. In the context of the rapid development of digital technologies, studying the potential and barriers to using AI assistants is extremely relevant for Ukrainian enterprises, as it helps them adapt to global trends. The study analyzes current trends, economic and organizational benefits, and the main barriers and challenges associated with introducing AI assistants in business in Ukraine. The paper applies a systematic approach to the analysis of scientific publications, statistical data, and the results of surveys of entrepreneurs. The article reviews global and national trends in the use of AI assistants, assesses the benefits and barriers to their implementation, and identifies the key factors that influence the integration of these technologies into business processes. The study results show that using AI assistants helps automate business processes, reduce administrative burden, and increase the efficiency of customer interaction. At the same time, the main obstacles to implementation in Ukraine include lack of awareness among entrepreneurs, high cost of technology, ethical issues, and competition between employees and technology. Nevertheless, most surveyed entrepreneurs see AI as a promising tool, are ready to invest in its implementation and recognize its significant potential to increase productivity. The study highlights the need to improve staff training, ensure the availability of software, improve the regulatory framework, and provide government support for innovation. The findings contribute to a deeper understanding of the current challenges and opportunities for integrating AI assistants in Ukrainian business, creating a basis for developing strategies for their effective implementation.